Reversing the surface charge of MSC‐derived small extracellular vesicles by εPL‐PEG‐DSPE for enhanced osteoarthritis treatment - Kai Feng (Taylor & Francis Group, 2021)
Abstract Mesenchymal stem cell‐derived small extracellular vesicles (MSC‐sEVs) possess a great therapeutical potential for osteoarthritis (OA) treatment. However, the steric and electrostatic hindrance of cartilage matrix leads to very limited distribution of MSC‐sEVs in cartilage and low bioavailability of MSC‐sEVs after intra‐articular injection. To overcome this, a strategy to reverse the surface charge of MSC‐sEVs by modifying the MSC‐sEVs with a novel cationic amphiphilic macromolecule namely ε‐polylysine‐polyethylene‐distearyl phosphatidylethanolamine (PPD) was developed in this study. Through incubation with 100 μg/ml PPD, positively charged MSC‐sEVs (PPD‐sEVs) were obtained, and the modification process showed nearly no disturbance to the integrity and contents of sEVs and exhibited good stability under the interference of anionic macromolecules. A more effective cellular uptake and homeostasis modulation ability of PPD‐sEVs than unmodified MSC‐sEVs to chondrocytes was demonstrated. More importantly, PPD‐sEVs demonstrated significantly enhanced cartilage uptake, cartilage penetration, and joint retention capacity as compared to MSC‐sEVs. Intra‐articular injection of PPD‐sEVs into a mouse OA model showed significantly improved bioavailability than MSC‐sEVs, which resulted in enhanced therapeutic efficacy with reduced injection frequency. In general, this study provides a facile and effective strategy to improve the intra‐articular bioavailability of MSC‐sEVs and has a great potential to accelerate the clinical practice of MSC‐sEVs based OA therapy.